2021
DOI: 10.3389/fbioe.2020.593448
|View full text |Cite
|
Sign up to set email alerts
|

Axial Micromotion Locking Plate Construct Can Promote Faster and Stronger Bone Healing in an Ovine Osteotomy Model

Abstract: Fixing bone fractures with controlled axial interfragmentary micromotion improves bone healing; however, the optimal type of implant construct for this purpose is still lacking. The present study describes a novel axial micromotion locking plate (AMLP) construct that allows axial interfragmentary micromotion of 0.3 or 0.6 mm. We investigated whether the AMLP constructs enhance bone healing compared to an ordinary locking plate (LP) using an ovine osteotomy model. The stiffness of the constructs was tested unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This motion resolves once a fracture has healed or fusion is complete. Fixation constructs are designed to provide relative and not absolute stability as some degree or micromotion is desirable to achieve a bony union [ 6 ]. Too much motion, however, at a fracture or fusion site can lead to nonunion and subsequent implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…This motion resolves once a fracture has healed or fusion is complete. Fixation constructs are designed to provide relative and not absolute stability as some degree or micromotion is desirable to achieve a bony union [ 6 ]. Too much motion, however, at a fracture or fusion site can lead to nonunion and subsequent implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…Local biomechanical environment is an important factor that affect the regeneration and remodeling of new bone ( 13 , 30 ). Additionally, studies have demonstrated that less rigid fixation and comparable motion improved bone healing, and interfragmentary micromotion was thought to be a prerequisite for healthy fracture union ( 31 , 32 ). The same notion applies to bone growth after prosthesis implantation inside a bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological bridge plating aids in preserving the blood supply, facilitating a functional reduction in complex fractures [31]. Some types of locking plates offer a comparatively stable fixation for fractures while allowing adjustments to reduce the stiffness [32,33]. Fracture treatment devices characterized by excessive stiffness have been reported to result in suboptimal outcomes, including delayed bone healing and failure of the healing process [17,34].…”
Section: Clinical Problems In Bridge Plating For Fracture Treatmentmentioning
confidence: 99%